Hiring managers tacit knowledge in the electronic Human Resource Management - حسين حسين وليد (Journal of Economics and Administrative Sciences, 2016)
Abstract This research aims to determine the nature of tacit knowledge relationship and its impact on building the electronic human resources management, as it constitutes the most prominent tacit knowledge resources owned by the Organization for being a stand out in the skill, knowledge and intellectual capacity of human resources, as the electronic human resources management is a contemporary trend that adopted by the organization in the performance of all tasks and duties related workers have remained in the contemporary environment in which it operates. and have indicated the research problem to the low level of awareness of the administration researched the importance of tacit knowledge and their role in building the electronic Human Resource Management Organization, and to achieve the goals Find resolution adopted as a tool head for data collection, which has been prepared on the basis of a number of measures ready after it has been subjected to measures of validity and reliability to fit with the main purpose of this research, has been selected the education sector as a field of application, as was the choice of the number of teaching staff working in the Faculty of Administration and Economics / University of Baghdad and by (57) singly as a sample for research, was used statistical program Ready (SPSS) in the introduction and analysis of research data and the most important statistical tools used in the analysis: "The percentage of recurrence, and the arithmetic mean, standard deviation and coefficient of variation, and the correlation coefficient (Spearman), and simple linear regression," have resulted in statistical tools for a number of Results mostly confirmed the existence of a link and the impact of a relationship with a significance of Statistically speaking between tacit knowledge and building the electronic human resources management, these results are consistent with the hypotheses basic and subsidiary from which the search, the researcher recommended the need to increase the interest of the surveyed organization studying how to activate the role of tacit knowledge among their employees and invest in the construction of the electronic human resources management.